Evaluation of the Adsorption Process Using Low Cost Agroindustry Residue for the Removal of Methylene Blue Dye - de Oliveira, Fabiano Mendonça; de Sousa, Priscila Afonso Rodrigues; de Melo, Edmar Isaias; Coelho, Luciana Melo (Orbital: The Electronic Journal of Chemistry, 2020)
The activities of the textile industry consume a lot of water, generating a high volume of effluents, contributing to the increase of contaminant levels. Adsorption has been pointed out as a promising technique for the removal of effluent dyes. Agroindustry wastes are alternative materials of low cost, since considerable quantities of these are discarded in the environment and already have been reported the potential of these materials as adsorbents in the removal of pollutants. In this sense, the present work evaluated the use of the orange peel as adsorbent material in the removal of the methylene blue dye in aqueous medium by adsorption. The characterization of the residue was evaluated using scanning electron microscopy and infrared spectroscopy. The time required for the system to reach equilibrium was 40 min, following the kinetics described by the Pseudosecond Order Parameters. The maximum adsorptive capacity verified was 62.89 mg g-1, following the Langmuir isotherm model, however the model that best fit was Freundlich, indicating adsorption in multilayers. In this way, the obtained results showed that the orange peel presents potential application as adsorbent in the treatment of organic pollutants in specific, cationic dyes present in liquid effluents.DOI: http://dx.doi.org/10.17807/orbital.v12i2.1422